Community Empowerment in Development Creative Economy through “Pahari” Rattan Crafts in Sabaru Kelurahan Sebangau Kota Palangka Raya - Dedy Ilham Perdana; Novia Lestary (Budapest International Research and Critics University, 2020)
Rattan woven handicrafts are creative economic enterprises that take advantage of local potential and also hone abilities and skills. Rattan is processed into handicraft items that have high selling value. The processing of handicrafts made from rattan is very attractive to the public with unique and distinctive motifs from Central Kalimantan. Empowerment of the community's economy through woven rattan handicrafts has good prospects for the future so that it can make the lives of people who are members of the pahari rattan craftsmen group prosperous. This research is a type of qualitative research. The data in this study were obtained by observation, interviews, and documentation. The main instrument in this study is the researcher himself with the help of observation guidelines, documentation guidelines, interview guides, and using other aids in the form of piles or cellphones, and writing instruments. The validity of the data was obtained by extension technique with participation, observation persistence and triangulation. Data analysis techniques are carried out by reducing data, presenting data, and drawing conclusions or verification. The results of this study indicate that (1) the process of making rattan woven bags, the process of designing, and preparing tools and materials. Production process: dye process, weaving process, assembly process and finishing process. (2) the motifs applied to the rattan woven bag craft in the Pahari Rattan Craftsmen Group are many motifs such as the lamiang motif on the ribbon tie, the dare bawak balanti motif, the dare sawang motif, the dare tie motif, the dare palapas tingang motif, the uhat djadjangkit motif, dare kilat mayambar, dare kambang malati motive, shoot dare rabung dare motif, dare anchor motif, daring rod garing dare motif, katimpun dare kambang motif, kumpang dare kumpang, dare boat motif, dare deer motif, and lamiang dare motif. (3) The types of bags produced by the Pahari Rattan Craftsmen Group are bags with various types of motifs typical of Central Kalimantan.